THE INHIBITION PROCESS ON SUCROSE DEGRADATION IN SUGAR CANE JUICE USING - T. Ikhsan Azmi, Sapta Raharja Prayoga Suryadarma dan Ani Suryani (Jurnal Teknologi Industri Pertanian, 2009)
The degradation of sucrose in sugar cane juice in process caused by inversion enzyme reaction and microorganism activity. The inversion sucrose caused by damage or maintenance of process equipment (downtime). The inhibition process on sucrose degradation obtained by inert gas bubbling using loop venturi reactor. The research finding inhibition of sucrose degradation technology process in sugar cane juice by Nitrogen gas bubbling using loop-venturi reactor. The research was carry out by variation of flow rate of sugar cane juice. There where 25 I/min, 20 I/min and 15 I/min. Loop-venturi reactor operated at gas velocity ranging 0.02 – 0.6 m/s and nozzle diameters was 5, 6, and 8 mm. The result was found that the gas holdup could be successfully inhibitited the sucrose degradation. The result showed, there are linear correlation between inhibition process and gas hold-up. Inhibition rate of sucrose degradation at flow rate sugar cane juice 25 I/min and gas velocity 0.6 m/s using nozzle diameter 6 mm and reactor temperature 70 oC, can be inhibite sucrose 4.2 %. Keywords: sugarcane juice, sucrose, loop-venturi reactor, gas hold-up, flow rate.